Quality with integrity: Working in partnership to conduct a program review - McKenny, Paige; Anderson, Catherine (International Journal for Students as Partners, 2019)
Quality assurance processes often include reductive quantitative metrics that view higher education through a neoliberal lens. This paper reports on a student-faculty partnership that conducted a quality review of an undergraduate program at a large research university and shows that working in partnership brings integrity and constructive complexity to the quality assurance process. The partnership laid the groundwork for realistic enhancements in the undergraduate program by weaving multiple, authentic perspectives from student and faculty stakeholders into the review. The authors also experienced profound growth in their sense of connection to each other and to the university community. These outcomes suggest that conducting quality assurance in partnership can destabilize traditional power structures and disrupt a transactional understanding of faculty-student relationships, while also satisfying regulatory requirements.